Особливості функціонування релейного захисту в розподілених системах тягового електропостачання - Сиченко, Віктор Григорович; Косарєв, Євген Миколайович; Данилов, Олексій Анатолійович; Губський, Петро Вячеславович; Зубенко, Василь Анатолійович; Пулін, Микола Миколайович (НТУ "ХПІ", 2018)
Впровадження альтернативних джерел електричної енергії у систему тягового електропостачання розподіленого типу підвищує енергетичну ефективність та надійність функціонування, але при цьому змінюється характер протікання енергообмінних процесів, що обумовлює необхідність врахування виникаючих змін струморозподілу для налаштування уставок релейного захисту. Така необхідність викликається збільшенням струмів короткого замикання в розподіленій системі живлення електрорухомого складу за рахунок появи в системі додаткових джерел енергії. Для виключення хибних спрацьовувань та забезпечення селективності необхідно застосовувати мікропроцесорні комплекси релейного захисту, які дозволяють більш точно встановлювати уставки спрацьовування швидкодіючих вимикачів.

The implementation of alternative sources of electric energy into a distributed traction power supply system improves the energy efficiency, but it is necessary to solve a number of tasks: to determine their impact on the stability of the traction substations, traction and other consumers connected to the traction substation buses taking into account allowable work modes of consumers; to take into account the features of connected generation types to electric railways networks; to provide the necessary reliability level of power supply for consumers with given qualitative characteristics. In the traction network with reinforcing points, the nature of the flow of energy-exchange processes changes, which makes it necessary to take into account the forthcoming changes in the distribution to adjust the settings of relay protection. Such a necessity is caused by increased short-circuit currents in the distributed traction power supply system due to the appearance of the additional energy sources in the system. In order to exclude false positives and provide selectivity, it is necessary to apply microprocessor relay protection complexes that allow setting more accurately the settings for the operation of high-speed circuit-breaker. In order to increase the reliability of functioning, it is useful to use the remote interlocking devices that at the presence of protection dead zones, inevitably eliminate the feeding of the short circuit point in the case of failure of feeder high-speed circuit-breakers.
Features of relay protection function in distributed traction power supply systems
Keywords: постійний струм; розподілене живлення; сонячна електростанція; джерела розподіленої генерації; СТЕ; ДРГ; тягові підстанції; ТП; коротке замикання; direct current; distributed power supply; solar power station